Premature Ductal Constriction and Reversible Early Isolated Right Ventricular Cardiomyopathy in a Neonate at Birth - Tyagi, Vernika; Chopra, Abhishek; Jain, Ashish (Journal of Fetal Medicine, 2019)
Cardiomyopathies are a group of diseases of the myocardium associated with mechanical and/or electrical dysfunction that usually exhibit inappropriate ventricular hypertrophy or dilatation. Neonatal CMs account for about 1% of childhood cardiac disease, with an estimated incidence of 10:100,000 live births, and are responsible for 10% of all paediatric cardiac deaths [1]. Among this, transient right ventricular hypertrophy (RVH) is a rare anomaly that is seen during the neonatal period. The various causes associated with right ventricular hypertrophy are maternal diabetes, metabolic causes, NSAID use and premature constriction of ductus. Present case is interesting as no cause could be found in this case of transient RVH.
Keywords: Neonatal cardiomyopathy; Transient right ventricular hypertrophy; Non compaction cardiomyopathy